2014
DOI: 10.2340/16501977-1874
|View full text |Cite
|
Sign up to set email alerts
|

Decanulation of patients with severe respiratory muscle insufficiency: Efficacy of mechanical insufflation-exsufflation

Abstract: Many ventilator users can be decanulated in outpatient clinics to continuous noninvasive intermittent positive pressure ventilatory support with mechanical insufflation-exsufflation used to increase vital capacity, SpO2, and autonomous ability to breathe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 27 publications
0
38
0
13
Order By: Relevance
“…is approach is complemented by advanced secretion management strategies i.e., air-stacking and mechanical insufflation exsufflation (MI-E) and also incorporates specifically designed protocols to decannulate tracheostomized patients to 24-hour full ventilatory support [5,6]. According to these protocols, an assisted PECF > 160 L/ min effected by a combination of MI-E and abdominal thrust is associated with a very high rate of tracheostomy decannulation success [110,120].…”
Section: Discussionmentioning
confidence: 99%
“…is approach is complemented by advanced secretion management strategies i.e., air-stacking and mechanical insufflation exsufflation (MI-E) and also incorporates specifically designed protocols to decannulate tracheostomized patients to 24-hour full ventilatory support [5,6]. According to these protocols, an assisted PECF > 160 L/ min effected by a combination of MI-E and abdominal thrust is associated with a very high rate of tracheostomy decannulation success [110,120].…”
Section: Discussionmentioning
confidence: 99%
“…Beck et al evaluated voluntary cough and found that in patients with severe respiratory muscle insufficiency and a PCF of less than 160 L/min, decannulation was unsuccessful due to difficulty in keeping the airway clear after extubation and decannulation [20]. Lasserson et al reported that PCF of involuntary cough was less than that of voluntary cough, explaining that this was related to differences between the two types of cough in terms of the functional organization of muscle activation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at the end of the MI-E treatment there is application of insufflation, which provides inspiration to appropriate functional residual capacity (Hull et al 2012). MI-E can be used with various interfaces on patients who are spontaneously breathing, intubated or tracheotomized (Miske et al 2004, Bach et al 2014.…”
Section: Combination Of Assisted Inspiration and Expirationmentioning
confidence: 99%